A Digital Halal Marketplace Adoption Model: The Roles of Perceived Halal Assurance, Trust, and Religiosity in Purchase Decisions - Bella Laila Rahmah; Salma Isfihany (Global Writing Academica Researching and Publishing, 2026)
The rapid expansion of digital commerce has transformed the halal marketplace, creating new opportunities while intensifying concerns regarding halal integrity, consumer trust, and religious compliance in online purchasing environments. This study aims to develop a conceptual digital halal marketplace adoption model by synthesizing the relationships among perceived halal assurance, trust, religiosity, and consumer purchase decisions. Employing a literature review approach, the study systematically examines and integrates contemporary scholarly evidence on halal digital ecosystems, consumer behavior, technology adoption, and Islamic marketing. The reviewed literature indicates that perceived halal assurance functions as a critical antecedent that reduces uncertainty and strengthens consumers' confidence in digital transactions. Trust consistently emerges as a mediating mechanism that reinforces consumers' willingness to engage with halal marketplace platforms and ultimately influences purchase decisions. Furthermore, religiosity shapes consumers' evaluation processes by strengthening their preference for halal-compliant products and platforms that align with Islamic principles. The synthesis also reveals that the interaction among halal assurance, trust, and religiosity provides a more comprehensive explanation of consumer decision-making than isolated examinations of these constructs. Based on these findings, this study proposes an integrated conceptual framework that explains digital halal marketplace adoption from both technological and Islamic behavioral perspectives. The proposed model contributes to the advancement of halal consumer behavior literature by consolidating fragmented theoretical perspectives into a coherent framework for future empirical validation. The findings further offer strategic insights for digital halal marketplace operators, policymakers, and halal certification authorities in enhancing consumer confidence and promoting the sustainable growth of the global digital halal economy.